Proceedings of the 1986 ACM Conference on Computer-Supported Cooperative Work - CSCW '86 1986
DOI: 10.1145/637069.637099
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration research in SCL

Abstract: The System Concepts Laboratory (SCL) of Xerox PARC is in the second year of a research program investigating the support and enhancement of collaboration. To begin, we explain our research goals and operationally define "collaboration" as we have chosen to study it. Then, we describe the environment in which the research takes place, including the two-site, distributed organization of SCL. In our first year, we have had many experiences that are relevant to understanding collaboration and we present a few of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Its inception can be influenced by many different factors, including the social distance between academics (McDonald, 2003), level of trust held by each academic (Goodman & Abel, 1986;Kraut et al, 1986), and the type of research being completed. It is the purpose of this study to determine the effects of one's citation patterns and geographic position have on an academic's propensities to collaborate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its inception can be influenced by many different factors, including the social distance between academics (McDonald, 2003), level of trust held by each academic (Goodman & Abel, 1986;Kraut et al, 1986), and the type of research being completed. It is the purpose of this study to determine the effects of one's citation patterns and geographic position have on an academic's propensities to collaborate.…”
Section: Discussionmentioning
confidence: 99%
“…A second factor that also must be taken into account in this study is the actual time taken to perform a collaborative project. Research has shown that, due to an increase in administrative tasks, the time taken to perform collaborative research is increased quite significantly (Goodman & Abel, 1986;Katz & Martin, 1997;Kraut et al, 1988). In addition to an increase in administrative tasks, there is also time lost in finding a suitable collaborative partner, or partners, and a problem that is suited to all academics involved.…”
Section: Visualisation Of Collaborative Processmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires an awareness of the interplay between technology and group productivity. Successful conferencing projects have had discoveries of seemingly unimportant human factors that flew in the face of technology -small modifications of either psychological or sociological import that created a good match between the capabilities of the systems and the tolerance, expectations, and needs of their user communities (Elliott 1993;Goodman and Abel 1986;Macedonia and Brutzman 1994;Mantei 1988;Root 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Studies encompassing technical and behavioral aspects of video use have been a mainstay of the literature in the computer supported cooperative work field. In 1986 Goodman and Abel [1] described a link between two conference rooms. The first session of CSCW '88 included a paper describing a desktop videoconferencing system [2] and an equally influential paper titled "Videoconferencing as a technology to support group work: A review of its failures" [3].…”
Section: Introduction: Summary Of a Research Threadmentioning
confidence: 99%